Gender-related Therapeutical Response to Apremilast: New Insights in a Tailored Management of Psoriasis - Trovato, Emanuele; Bardazzi, Federico; Di Lernia, Vito; Corazza, Monica; Lasagni, Claudia; Prignano, Francesca (Dermatology Practical & Conceptual, 2025)
Introduction: Psoriasis is a chronic immune-mediated skin condition. One of the intriguing challenges in studying psoriasis has been identification of correlations between this disease and gender and body weight. Objective: A multicenter retrospective study was conducted among patients with moderate-to-severe psoriasis who attended the outpatient clinics of 6 University Hospitals in Italy. The effects of apremilast on weight and body mass index (BMI) according to gender after 24 weeks and 48 weeks of therapy were considered. Methods: We enrolled retrospectively 120 adult patients with moderate-to-severe psoriasis who underwent apremilast treatment for at least 24 weeks. Baseline characteristics, including age, gender, psoriasis area severity index (PASI), comorbidities, smoking and alcohol habits, relevant medical history and previous psoriasis systemic and biologic treatments were recorded. Weight and body mass index (BMI) were evaluated at baseline (T0) and at 24 (w24) and 48 weeks (w48). A descriptive statistical analysis has been performed. Results: The analysis showed a significant reduction in body weight in females at w24 and w48 (p < 0.001), with a mean difference of −2.6 kg at w24 and of -5.7 kg at w48. We observed a reduction of weight of 3.6% at w24, and 7.9% at w48. Similar assessments were also observed for BMI, which was reduced in women by 3.6% at w24 and 8% at w48. In men, no changes in weight and BMI were observed at w24 and/or w48. Conclusion: Understanding the interplay between psoriasis, gender, and body weight is essential for effective disease management and improving patient outcomes.